A Synthesized Study of the Spatiotemporal Evolution of Central Yellow Sea Mud Depositional Processes During the Holocene - Zhong, Fuchang; Xiang, Rong; Zhang, Lanlan; Yang, Yiping; Zhao, Meixun; Zhou, Liping (Frontiers in Earth Science, 2021)
The spatial distribution patterns of central Yellow Sea Mud (CYSM) thicknesses and their temporal evolution during the Holocene are here updated using data from 10 new cores, in combination with the previously-published data for 64 cores from this area. Of these 74 cores, 15 exhibit clear AMS 14C dating constraints. Three subareas of mud deposition can be delineated using analyses of spatiotemporal mud thickness distributions and the variations between these. A depocenter subarea, with mud thicknesses >4 m, lies in the northwestern part of the CYSM; the mean sedimentation rate (SR) is relatively high in this subarea, with two high SR stages occurring at ∼6.1–5.4 ka and ∼4–2.5 ka. An adjacent subarea surrounds the depocenter subarea; this subarea has mud thicknesses between 2 and 4 m, and a high mid-Holocene SR which evinces a gradually decreasing trend after 5 ka. A distal periphery subarea lies in the eastern part of the CYSM, with mud thicknesses between 0.5 and −2 m, and a low mean SR that has been generally stable over the last 7 ka. Our results indicate that both sedimentary sources and hydrological dynamics played important roles in the formation of CYSM. The Yellow River may be the principal sedimentary source for CYSM, as mud thickness decreases gradually from northwest to southeast. Different mud subareas appear to be affected by different hydrological dynamics: in the depocenter subarea, oceanic current fronts seem to play an important role in mud deposition, while in the adjacent subarea and the distal periphery subarea, weak tidal currents appear to be the dominant depositional control. The generally decreasing trend in the SR of the adjacent subarea indicate that the East Asian winter monsoon (EAWM) potentially controlled changes in CYSM sedimentary sources after 7 ka.